William Allingham in his contexts - Mooney, Wendy (Trinity College (Dublin, Ireland). School of English, 2012)
This thesis examines the work of William Allingham within its social, cultural and historical contexts in order to clarify the true influences behind the Donegal poet's poems and ballads and the driving force behind his essays and articles. Allingham's early Irish landscape poems contained in Poems (1850) and The Music Master, A Love Story; and Two Series of Day and Night Songs (1855), and his efforts to establish his distinctiveness in England through a common Celticism often inspired by Irish landscape painting are assessed - as is the impact of the Famine, which makes its presence felt in the states and images of marginality described in his early poems.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin.